Closing performances of double‐gap laser‐triggered vacuum switch. Issue 2 (27th October 2020) - Chen, Zhanqing; Duan, Xiongying; Liao, Minfu; Zhang, Hao; Zhang, Ming; Zou, Jiyan
Abstract: To develop high‐voltage‐pulsed power switches with better performances, a multi‐gap laser‐triggered vacuum switch is proposed in this study. Based on established test prototype for double‐gap laser‐triggered vacuum switch, closing processes of double‐gap laser‐triggered vacuum switch are discussed combined with laser‐produced plasma. Closing performances of double‐gap laser‐triggered vacuum switch under different gap polarity configurations, operating voltages, laser energies and laser split ratios are investigated. Closing time delay characteristics of double‐gap laser‐triggered vacuum switch and single‐gap laser‐triggered vacuum switch are compared later. The test results prove that, affected by the imbalanced developed initial plasma between gaps, double‐gap laser‐triggered vacuum switch with two positive gaps and 1:1 laser split ratio presents best closing performances than other switches. With the rise of laser energy, closing delay time and jitter time of double‐gap laser‐triggered vacuum switch both decrease, while the influences from increasing voltages are weak. Closing delay time of P–P type double‐gap laser‐triggered vacuum switch can be controlled within 103 ± 1.5 ns under 90 mJ laser energy, and it is about 10 ns longer than single‐gap laser‐triggered vacuum switch. For some direct current applications with changing voltage directions, P–N type double‐gap laser‐triggered vacuum switch with 1:1 laser split ratio shows more stable closing performances. In addition, closing performances of double‐gap laser‐triggered vacuum switch can be further improved by optimizing the developments of initial plasma in series gaps.